Hambatan Perkembangan Motorik Kasar pada Anak Usia 6 Tahun Ekplorasi Awal Faktor Resiko Sindrom Tourette - Gracenia Debby Azzahrah; Evania Yafie; Nur Anisa (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to explore gross motor developmental delays in 6-year-old children as an early indication of possible Tourette syndrome. Tourette syndrome is a neuropsychiatric disorder characterized by the emergence of spontaneous movements and sounds (tics) that are not realized and can interfere with the child's daily activities. In this study, a qualitative approach was used with a case study method on a boy in Malang City who showed symptoms of motor and vocal tics. Data collection was carried out through observation, in-depth interviews with teachers and parents, and documentation of the child's activities in the home and school environment. The results of the observation showed that the child had difficulty maintaining balance and showed spontaneous movements such as shaking his head, blinking, and clearing his throat repeatedly. These symptoms do not always appear consistently and occur more often when the child is tired or mildly stressed. Data analysis showed that motor delays were not caused by muscle disorders, but by an imbalance in neurological regulation that affects movement coordination. The main risk factors come from daily habits such as excessive use of gadgets, lack of rest time, and unstable emotional responses. The treatment carried out involves a combination of medication from a neurologist and environmental support such as reducing stress triggers, regulating playtime, and an inclusive educational approach. This study emphasizes the importance of early detection, holistic intervention, and ongoing support from families and educators in dealing with children with Tourette syndrome symptoms so that motor delays do not develop into more serious disorders.